Individual Time Preferences and Energy Efficiency - Newell, Richard G.; Siikamäki, Juha (American Economic Review, 2015)
We examine the role of individual discount rates in energy efficiency decisions using evidence from an extensive survey of US homeowners to elicit preferences for energy efficiency and cash flows over time. We find considerable heterogeneity in individual discount rates. We also find that individual time preferences systematically influence willingness to invest in energy efficiency, as measured through product choices, required payback periods, and energy efficiency tax credit claims. Education is a key driver of individual discount rates. Our findings highlight the importance of individual discount rates to understanding energy efficiency investments, the energy-efficiency gap, and policy evaluation.